Motivations and values associated with combining sex and illicit drugs ('chemsex') among gay men in South London: findings from a qualitative study. (12th August 2016) - Weatherburn, P; Hickson, F; Reid, D; Torres-Rueda, S; Bourne, A
Abstract : Objectives: There is considerable public health concern about the combining of sex and illicit drugs (chemsex) among gay men. With a view to inform supportive therapeutic and clinical interventions, we sought to examine the motivations for engaging in chemsex among gay men living in South London. Methods: Community advertising recruited 30 gay men for qualitative semi-structured interview. Aged between 21 and 53 years, all lived in South London in the boroughs of Lambeth, Southwark and Lewisham and all had combined crystal methamphetamine, mephedrone and/or γ-hydroxybutyric acid/γ-butyrolactone with sex in the past 12 months. Transcripts were subjected to a thematic analysis. Results: We broadly distinguished two groups of reasons for combining sex and drugs, within which we described eight distinct motivations. The first major group of motivations for combining drugs with sex was that drugs provide the means by which men can have the sex they desire by increasing libido, confidence, disinhibition and stamina. The second major group of motivations for chemsex was that drugs enhance the qualities of the sex that men value. Drugs made other men seem more attractive, increased physical sensations, intensified perceptions of intimacy and facilitated a sense of sexual adventure. Conclusion: Analysis revealed that sexualised drug use provides both motivation and capability to engage in the kinds of sex that some gay men value: sex that explores and celebrates adventurism. Those services providing (talking) interventions to men engaging in chemsex should consider these benefits of sexualised drug use alongside the harms arising.